(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The articlediscusses various aspects of obtaining drugs against parasites and parasitic diseases based on essential oil plants of the Kyrgyz Ala-Too. Long before the appearance of synthesized drugs, animals ate certain types of essential oil plants to get rid of various parasites. It is known that some wild and domestic animals with certain diseases eat poisonous, strongsmelling plants, the medicinal properties of which cannot yet be fully explained. As a result of studies of the studies plants, a pronounced therapeutic and prophylactic effect on parasitic diseases was shown. However, the proposed plants and their action separately for these diseases are not highly effective. In order to enhance their preventive effect, complex recipes, doses, premixes, infusions and extracts from the studied plants were developed.